PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI ASN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN SITUBONDO - Zahro, Fatimatus; Karnadi, Karnadi; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2024)
Work discipline is very important to ensure the maintenance of orderly implementation of each task without work discipline it is very difficult for a company to succeed, in enforcing work discpline is subject to punishment. A good work environment also influences. And work motivation is very important in encouraging employees to achieve a goal. This research analyzes and tests the role of work discpline, work environment, work motivation on the performance of ASN employees through job satisfaction as an intervening variable at the situbondo district education and culture office. The research is explanatory research, the population in this research are employees of the Situbondo education and culture service. The sampling technique was determined by quota sampling. Data analysis and hypothesis testing in this research used the Structural Equation Model – Partial Least Squares (PLS – SEM) The result of the direct influence hypothesis test using the smart PLS 3.0 application, show that work discipline has a significant effect on performance, work discipline has a significant positive effect on job satisfaction, work environment has a significant positive effect on job satisfaction, motivation has a significant effect on performance, motivation has a significant positive effect on job satisfaction. The result of the indirect influence hypothesis test show that the work discipline variable on job satisfaction through performance has a significant positive effect, the work environmance has a significant positive effect, the work environment on job satisfaction through performance has a significantly positive effect. Motivation on job satisfaction through performance has a significant positive effect.